Understanding the management of osteoarthritis: A qualitative study of GPs and orthopaedic surgeons in Tasmania, Australia. Issue 4 (December 2021) - Sutton, Laura; Jose, Kim; Betzold, Alana; Hansen, Emily; Laslett, Laura; Makin, Jennifer; Winzenberg, Tania; Balogun, Saliu; Aitken, Dawn
Abstract: Objective: Using a qualitative design this study aimed to 1) explore the attitudes towards and understanding of osteoarthritis (OA) held by Tasmanian general practitioners (GPs) and orthopaedic surgeons, 2) gain a deeper understanding of conservative and surgical management and 3) identify key barriers and challenges. Design: Purposive sampling was used to recruit 17 ​GPs and 10 surgeons from Tasmania, Australia. Semi-structured interviews were audio-recorded, transcribed, coded, and thematically analysed to document understanding of OA, management and treatment decision making. Results: GPs and surgeons had a shared understanding of the cause and management of OA which aligned well with evidence-based best practice. Most GPs acknowledged that severity of disease on an X-Ray does not correlate well with symptoms, although some GPs reported always using imaging to support their diagnosis. Conservative management was highly supported by all interviewees, focussing on exercise and/or physiotherapy. Key treatment barriers included managing poor patient understanding of OA, unrealistic expectations for treatment, lack of patient motivation and scepticism towards exercise, and cost and accessibility of conservative treatment options. Surgery was considered a suitable option when conservative management options had been exhausted. Conclusion: This study uniquely interviewed GPs and surgeons from the same population, capturing two crucial areas of OA management. Some key barriers to treatment were identified and options for improving treatment include creating opportunities for increased patient education about OA, enhanced accessibility to OA conservative management programs along with improved reimbursement models supporting conservative management as first-line OA treatment.